The Unresolved History and Genealogy of Forced Displacement in Mexico - Robledo Silvestre, Carolina (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2016)
This article reconstructs symbolic elements and practices that underline the recent dispute over the characterization and nature of “forced displacement” in Mexico. The point of departure for this analysis is that of the contemporary Mexican context in which political and criminal violence are often interlinked. This has resulted in new challenges when attending to the demands of the victims of these crimes. These new challenges necessitate a questioning of the limits and scope of human rights discourse in relation to forced displacement in Mexico. The conclusions of this study emphasize the necessity to “vernacularize” the typology of forced displacement in order to challenge the forms of exclusion established by the existing definitions.